A produção de vídeo estudantil na prática docente: uma forma de ensinar - Silva, Josias Pereira da (2014)
Technology reduces the distance between people, enabling non-technical users to become content producers. Children and young people have tools like mobile, tablet and camera for pictures and filming. Thus, they create and exhibit their productions in websites, exchange photos, information on social network, in spaces in which their culture is debated and accepted. In order to know whether and how the school uses these technologies in video production, we investigated the communicative practice of teaching with the use of technological equipment and with the production and video making, by a teacher and his students within the school space. For this analysis, we developed a case study with a teacher from the city of Guaíba, Rio Grande do Sul, Southern, Brazil. The subject was chosen because of his historical and social importance with the video production conducted in schools from this city. The research used the presuppositions of Pedagogy of Communication and Neuroscience to analyze how the practice this teacher is done with video making in classroom. To this end, we carried out a qualitative research, having these instruments: open interviews with this teacher and students and classroom observations. The data collected showed that the teacher worked in the transition between the traditional and the emerging paradigm. The data also indicate that the video production stimulates and encourages the dialogue and the collective construction of knowledges by students under the guidance of a teacher. The classes, besides providing enjoyment and involvement for the students, contribute to the learning of different contents of the curriculum. It was noticed, during classes, a sensitive teacher, concerned and responsible with the content addressed. A teacher who understands the basics of audiovisual technology, allowing the students to conduct research in audiovisual production. A teacher who teaches making the skills of students emerges through the video making production. This action has the characteristics of the emerging paradigm, since the teacher provides mediation between students, technologies and content.